The Role of Monitor Technicians in Enhancing Alarm Response. Issue 1 (June 2013) - Crandall, Beth; Papautsky, Elizabeth Lerner; Grome, Anna; Dressman, Kathy; Greenberg, James; Geiser, Maria
We report a study of monitor alarm response conducted in the newly designed Transitional Care Center (TCC) at Cincinnati Children's Hospital Medical Center. A key component of the new TCC design has been the development and implementation of a Monitor Technician (MT) position. We examined the MT role from a human factors perspective, with particular focus on the MT's coordination and communication with nurses (RNs) and respiratory therapists (RTs). We conducted observations and Cognitive Task Analysis interviews of MTs, RNs, and RTs. In this paper, we describe the value of the MT's role and define the challenges associated with the MT's responsibilities. MTs serve an important support function, but they face challenges in locating RNs/RTs to respond to alarms and at times, may be the only "eyes on" the patients, making training and preparation a critical aspect of the MT's function. In response to findings, CCHMC has taken a number of steps to improve alarm and alert responses and provide further support to the MT's role. The current study serves as a demonstration of the principles and methods that human factors can offer to healthcare organizations to support patient safety and quality of care.